2017
DOI: 10.1021/acs.est.7b02114
|View full text |Cite
|
Sign up to set email alerts
|

Human Exposure to Legacy and Emerging Halogenated Flame Retardants via Inhalation and Dust Ingestion in a Norwegian Cohort

Abstract: In this study, we estimated human exposure to polybrominated diphenyl ethers (PBDEs), hexabromocyclododecanes (HBCDDs), and several emerging flame retardants (EFRs) via inhalation and dust ingestion. Sixty indoor stationary air samples, 13 personal air samples, and 60 settled dust samples were collected from a Norwegian cohort during winter 2013. PBDEs showed the highest median concentration in dust (1200 ng/g), followed by EFRs (730 ng/g) and HBCDDs (190 ng/g). The PBDE concentrations in dust were mainly driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
38
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 53 publications
(115 reference statements)
12
38
5
Order By: Relevance
“…Compared with the international studies, the median level of DBDPE in this study (185.4 ng/g) was an order of magnitude lower than that in Swedish indoor dust (1700 ng/g) [47]. However, the median concentration of DBDPE in USA [25], UK [29] and Norway [31] was 2.2, 2.1 and 2.6 times lower than that in this study. The levels of DBDPE in house dust detected from different countries varied in two orders of magnitude; DBDPE concentrations in this study were generally moderate, while DBDPE in house dust from Sweden [47] and Spain [33] exhibited elevated concentrations ( Fig.…”
Section: Dbdpecontrasting
confidence: 86%
See 2 more Smart Citations
“…Compared with the international studies, the median level of DBDPE in this study (185.4 ng/g) was an order of magnitude lower than that in Swedish indoor dust (1700 ng/g) [47]. However, the median concentration of DBDPE in USA [25], UK [29] and Norway [31] was 2.2, 2.1 and 2.6 times lower than that in this study. The levels of DBDPE in house dust detected from different countries varied in two orders of magnitude; DBDPE concentrations in this study were generally moderate, while DBDPE in house dust from Sweden [47] and Spain [33] exhibited elevated concentrations ( Fig.…”
Section: Dbdpecontrasting
confidence: 86%
“…In this study, the full detection frequency of BTBPE indicates the extensive use of this emerging compound in indoor environment. The median level of BTBPE (14.49 ng/g) was very comparable to that in USA [25], UK [29], and Pakistan [39], but was three-to-five times lower than reported levels in Norway [31] and Spain [33]. As a whole, the concentrations of BTBPE presented in this study were of middle level compared with the international studies ( Fig.…”
Section: Btbpesupporting
confidence: 62%
See 1 more Smart Citation
“…The dust concentrations found in the preschools were lower compared to most other recent studies on BFRs in different indoor settings (Table 2). 18,19,22,23,[45][46][47] This could be due to the diverse indoor settings among the different studies, as well as the different age of the inves- The DFs and concentrations of BFRs in the indoor air in our study were low, as previously discussed (Table 1). However, αDBE-DBCH and βDBE-DBCH were frequently detected in LEP C with a maximum concentration of 8400 pg/m 3 and 18 000 pg/m 3 , respectively.…”
Section: Comparison To Other Studiesmentioning
confidence: 51%
“…This skewed the GM and arithmetic mean (AM) since non-detects were replaced with half their MDL values and the GM and AM were found to be consistently higher in our study compared to other studies reporting on BFRs in indoor air, see Table 2. 19,23,[46][47][48] Studies of BFRs on window surfaces are to date very scarce (Table 2). However, a recent study from the Czech Republic found DBE-DBCH and TBCO isomers, PBT and TBP-DBPE on window surfaces in home environments at higher concentrations compared to our results.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%